2021
DOI: 10.32718/ujvas4-3.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the state of industrial water bioresources in fish areas of Ukraine

Abstract: Agriculture, fisheries, and the food industry play a key role in ensuring the country's food security. The modern fishing industry in Ukraine is a highly industrial, capital-intensive, integrated production with high production costs, which is designed to ensure the socio-economic development of many coastal regions and provide the population with valuable protein products necessary for healthy eating. The total volume of extracted aquatic organisms in III and IV zones of aquaculture of Ukraine was studied; dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Останніми роками аквакультура активно розвивається у всьому світі, темпи середньорічного приросту її продукції складають приблизно 11 %. За прогнозами аналітиків, обсяги вирощування гідробіонтів найближчим часом перевищать об'єми вилову у Світовому океані (Burhaz et al, 2021).…”
Section: вступunclassified
“…Останніми роками аквакультура активно розвивається у всьому світі, темпи середньорічного приросту її продукції складають приблизно 11 %. За прогнозами аналітиків, обсяги вирощування гідробіонтів найближчим часом перевищать об'єми вилову у Світовому океані (Burhaz et al, 2021).…”
Section: вступunclassified
“…Researchers [4][5][6] investigated the dynamics of catch of hydrobionts by regions and fisheries zones on the territory of Ukraine from 2005 to 2020. It was found that production significantly decreased (up to 70-80%) in The state of use of fish resources in small reservoirs of the Rivne оblast almost all regions of Ukraine [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Сучасна рибна галузь України -це високоіндустріальне, капіталомістке, інтегроване виробництво з високою собівартістю продукції, яке покликане забезпечити соціальноекономічний розвиток багатьох приморських регіонів і забезпечити населення повноцінними білковими продуктами, необхідними для здорового харчування (Burhaz et al, 2021).…”
unclassified